IMPROVING STUDENTS’ WRITING ACHIEVEMENT IN NARRATIVE TEXT THROUGH ANIMATION MOVIE AT THE FIRST GRADE OF SMKS BM SINAR HUSNI 1 - Mima Dwiyana; Dwi Suci Amaniarsih (Universitas Potensi Utama, 2021)
This research was motivated by the in that case, some of the teachers still used this method to teach. The use of animated film media can be used as a teaching medium for teachers, especially in learning to write narrative text. This study aims to answer the following questions: (1) How is the implementation animation movie in teaching narrative text at class X AK 1 students of SMKS BM Sinar Husni 1 Helvetia?, (2) How is the ability of X AK 1students SMKS BM Sinar Husni 1 Helvetia in writing narrative text before and after using animation movie?, (3) How can animation movie improve students’of class X AK 1 of SMKS BM Sinar Husni 1 Helvetia achievement in writing narrative text?